2015
DOI: 10.1186/s13045-014-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin like growth factor binding protein 7 (IGFBP7) expression is linked to poor prognosis but may protect from bone disease in multiple myeloma

Abstract: BackgroundInsulin like growth factor binding protein 7 (IGFBP7) is a secreted protein binding insulin like growth factor 1 (IGF-1), insulin, vascular endothelial growth factor A (VEGFA), and activin A. It antagonizes bone morphogenetic proteins and is involved in the tumour propagation of solid as well as haematological malignancies. Its role in multiple myeloma (MM) is not defined so far. We therefore aim here to investigate its prognostic and pathophysiological role in MM.MethodsThe clinical significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…Recently, evidence has revealed that IGFBP7 plays an important role in bone formation. IGFBP7 may exert protective effects against bone disease in multiple myeloma (14). IGFBP7 is methylated in subchondral bone (15, 16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, evidence has revealed that IGFBP7 plays an important role in bone formation. IGFBP7 may exert protective effects against bone disease in multiple myeloma (14). IGFBP7 is methylated in subchondral bone (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…PTH, a stimulator of bone formation, increases IGFBP7 expression in osteoblasts (17). Moreover, IGFBP7 may protect against bone disease in multiple myeloma (14). IGFBP7 is related to subchondral bone sclerosis (15, 16) and neutralizes the inhibitory effects of activin A on osteoblast development (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could mean that the IGFBP complex remains intact in the circulation [153]. In addition, gene expression levels of the so-called IGFBP7 gene, also known as MAC25, Prostacyclin-Stimulating Factor, Tumor-Derived Adhesion Factor, or PGI2-Stimulating Factor, have been linked to poor prognosis [154]. IGFBP7 is not, however, a high affinity IGF binding protein and is not generally considered part of the extracellular IGF system [155].…”
Section: Diagnostic and Prognostic Potential Of The Igf System In MMmentioning
confidence: 99%